Effect of Nuclear Radiation Generated Thermal Spike on Degradation Reaction Kinetics of a Polymer SSNTD and Its Impact on Track Diameter (Journal of Atomic, Molecular, Condensed Matter and Nano Physics, 2022)
It has been extensively studied that high polymer form an important group of materials used for solid state nuclear track detectors (SSNTD). The radiation induced damage not only leave tracks for microscopic examination but also change other physical properties of the material. One of them being the average molecular mass of the polymer. The change in this parameter which is induced by the radiation exposure can be studied and can give an estimate of the number of polymer chain scission, which has a direct influence on the track diameter and can give an estimate of the energy of radiation deposited inside the sample. From this the energy of the incoming particle flux can be calculated. In this paper a relationship between polymer degradation as given by the extent of the depolymerization reaction, the track diameter and energy of the incoming particle is sought.
Keywords: SSNTD; Thermal Spike model; Polymers; Solid State reaction kinetics